THE GREAT IMAGE OF OUR YUNUS RAJABI NATIONAL MUSIC - Topildiyev Saidmurod Odiljon ugli (International Engineering Journal For Research & Development, 2022)
Yunus Rajabiy [1897.5 (17) .1 Tashkent - 1976.23.4] - composer, singer and musician (nay, dutar), collector of Uzbek musical heritage. People's Artist of Uzbekistan (1953), Academician of the Academy of Sciences of Uzbekistan (1966).